Reproductive empowerment and contraceptive self-care: a systematic review. Issue 2 (1st January 2022) - Burke, Holly M.; Ridgeway, Kathleen; Murray, Kate; Mickler, Alexandria; Thomas, Reana; Williams, Katie
Abstract: Contraceptive self-care interventions are a promising approach to improving reproductive health. Reproductive empowerment, the capacity of individuals to achieve their reproductive goals, is recognised as a component of self-care. An improved understanding of the relationship between self-care and empowerment is needed to advance the design, implementation and scale-up of self-care interventions. We conducted a systematic review of the peer-reviewed and grey literature published from 2010 through 2020 to assess the relationship between reproductive empowerment and access, acceptability, use or intention to use contraceptive self-care. Our review adheres to PRISMA guidelines and is registered in PROSPERO (ID CRD42020205235). A total of 3036 unique records were screened and 37 studies met our inclusion criteria. Most studies were conducted in high-income countries, were cross-sectional and had high risk of bias. Almost half included only women. Over 80% investigated male condoms. All but one study focused on use of self-care. We found positive relationships between condom use self-efficacy and use of/intention to use condoms. We found similar evidence for other self-care contraceptive methods, but the low number of studies and quality of the evidence precludes drawing strong conclusions. Few studies assessed causal relationships between empowerment and self-care, indicating that further research is warranted. Other underexplored areas include research on power with influential groups besides sexual partners, methods other than condoms, and access and acceptability of contraceptive self-care. Research using validated empowerment measures should be conducted in diverse geographies and populations including adolescents and men.